THE SEE SUBTYPE VERBS IN ENGLISH AND WOLIO LANGUAGES: A SEMANTIC APPROACH TO GRAMMAR - Nur Melansari; Nining Syafitri (English Education Journal, 2020)
This research aimed to investigate See subtype verbs in English and Wolio languages: the meanings and grammatical properties. The research is descriptive qualitative research. The sources of the data in this research include events, information, and documents. The techniques of collecting data are observation and interview. The data were analyzed through some steps: data reduction, data display, and conclusion and verification. The result shows that the English See subtype verbs identified are see, hear, smell, taste, feel, observe, notice and perceive. While the Wolio See subtype verbs identified are kamata, rango, bou, penami, namisi, and tuminda. In the aspect of meaning, the Wolio See subtype verbs do not always have the same function with English in the use. Some verbs in Wolio language have more wide semantic range, such as ‘kamata’ and ‘namisi’. ‘Kamata’ refers to become aware of somebody/something by using of eyes either in a glance or over period of time and carefully or not. In addition, ‘kamata’ also can be used to see a movie, witness the accident, and observed somebody or something. ‘namisi’ also can cover feel and perceive. Though it is a transitive and intransitive verb at once, but the passive sentence of this verb is not allowed. In addition, this verb also does not have the imperative form when it refers to ‘perceive’. Contrast with ‘tumindaea’ that has more narrow semantic meaning. ‘tumindaea’ is just used to pay attention or notice somebody or his/her speech or advice.